Efforts to Stabilize Blood Pressure in Hypertensive Patients with Management of Hypertension Therapy Gymnastics Training - Susanti Susanti; Nabila Nurmalina Ramadhani; Putri Puspitasari (Journal of Health Community Service, 2022)
Hypertension is a type of degenerative disease whose prevalence is increasing over time. The success of hypertension management is influenced by daily activities for people with hypertension to control blood pressure. The purpose of implementing this intervention is to reduce blood pressure and control the blood pressure of hypertensive patients by doing hypertension therapy exercises. The training used is a training method by collaborating with hypertension exercise movements in young adults, using a sample of 30 hypertension sufferers in RT 23 RW 05, Kedung Rejo Village, Waru District, Sidoarjo Regency. The application of hypertension therapy exercise is carried out three times a week with a duration of 30 minutes, and evaluation of the ability of hypertension therapy exercise and evaluation of blood pressure at the beginning and end of the meeting. The results of the evaluation of the ability of hypertension therapy exercise according to operational standards (SOP) with the results of blood pressure initially seven people (23.3%) with normal high criteria (130-139/85-89mmHg) to 23 people (76.7%) after being given hypertension therapy gymnastics training activities. Hypertension therapy gymnastics can lower blood pressure and be modified through young adult gymnastics movements that can be applied routinely to people with hypertension. The results of this training activity are expected to increase the self-awareness of hypertension sufferers to increase gymnastic activities as a non-pharmacological treatment so that their blood pressure remains normal and as a basis for developing further interventions.